2019
DOI: 10.1017/jfm.2019.478
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic microstreaming near a plane wall due to a pulsating free or coated bubble: velocity, vorticity and closed streamlines

Abstract: Acoustic microstreaming due to an oscillating microbubble is analytically investigated to obtain the circular streaming motion adjacent to a nearby wall. Classical theory due to Nyborg is carefully derived in the radial coordinates. The theory is used to obtain the flow field and the vortical motion caused by the microbubble motion. The length of the vertices are decreasing when the microbubble is excited at distances close to the rigid wall, while the maximum shear stress is increasing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Using a combination of particle image velocimetry (PIV) and theoretical analysis, other researchers have shown that the shear stresses induced by acoustic microstreaming flows around microbubbles are significantly higher (~19 Pa) than the shear stresses induced by normal blood flow (~0.5-2 Pa), resulting in sonoporation [102]. These and several other theoretical and experimental studies showed that acoustic microstreaming may be a major mechanism of sonoporation [105][106][107]. Furthermore, microstreaming flow pattern is strongly dependent on the driving ultrasound frequency, microbubble size, pressure amplitude, properties of surrounding media as well as oscillation mode of microbubbles, which might explain why sonoporation and intracellular delivery of molecules are strongly affected by these parameters, as noted in several other studies [102,[108][109][110].…”
Section: Acoustic Microstreamingmentioning
confidence: 97%
“…Using a combination of particle image velocimetry (PIV) and theoretical analysis, other researchers have shown that the shear stresses induced by acoustic microstreaming flows around microbubbles are significantly higher (~19 Pa) than the shear stresses induced by normal blood flow (~0.5-2 Pa), resulting in sonoporation [102]. These and several other theoretical and experimental studies showed that acoustic microstreaming may be a major mechanism of sonoporation [105][106][107]. Furthermore, microstreaming flow pattern is strongly dependent on the driving ultrasound frequency, microbubble size, pressure amplitude, properties of surrounding media as well as oscillation mode of microbubbles, which might explain why sonoporation and intracellular delivery of molecules are strongly affected by these parameters, as noted in several other studies [102,[108][109][110].…”
Section: Acoustic Microstreamingmentioning
confidence: 97%
“…With flexibility and scalability similar to microrobots, their cost is much lower. Microbubbles have complex fluid and vibration models [33], especially for the Bjerknes force generated by the interaction of multiple bubbles [34,35], and the control method means that it is also one of the objects of micromanipulation [36]. The study of microbubbles has its own field.…”
Section: Appl Sci 2019 9 X For Peer Review 3 Of 25mentioning
confidence: 99%
“…Therefore, particles can still be dynamically analyzed by the method described above. Hydrodynamics is highly nonlinear, and studies related to micromanipulation are numerous and complex [33,47,48]. Here, we summarize the simple mechanical principles involved in streaming flow rather than precise numerical solutions.…”
Section: Force Acting On the Target In Streaming Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40][41] UCA oscillations also cause acoustic microstreaming ows surrounding the microbubble leading to enhanced mixing and shear stress experienced by nearby cell membranes. 31,42 The shear stress is believed to increase membrane permeability or excite mechanosensitive ion channels, potentially allowing for therapeutic drug delivery to the cells. 43,44 However, UCAs are restricted to the vascular system as they are too large to permeate outside of the blood vessels.…”
Section: Introductionmentioning
confidence: 99%